The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9nr05885k
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy-driven self-assembly of amphiphilic Janus dendrimers into onion-like vesicles: a Janus particle model

Abstract: The characteristics of concentration-dependent self-assembly of compact dendrimers into onion-like dendrimersomes are investigated using computer simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Many experiments and simulations have shown that Janus NPs can self-assemble into micelles with various structures. 17–19,32,33 To weaken the tendency of self-assembly for Janus NPs, we increased the parameters ε AO and ε BW for a high solubility, but the E binding is meanwhile reduced. When E binding is decreased to be equal to or smaller than 9.0 k B T , free Janus NPs could be observed in liquids (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experiments and simulations have shown that Janus NPs can self-assemble into micelles with various structures. 17–19,32,33 To weaken the tendency of self-assembly for Janus NPs, we increased the parameters ε AO and ε BW for a high solubility, but the E binding is meanwhile reduced. When E binding is decreased to be equal to or smaller than 9.0 k B T , free Janus NPs could be observed in liquids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Janus NPs with two distinct faces have many fascinating properties, such as the capability to form clusters with a controlled size and shape. 17–19 It was noticed that Janus NPs with high interfacial activity could reduce the interfacial energy to an extent even larger than that of NP surfactants. 20–22 However, it is puzzling that, until now, experiments successfully exploiting Janus NPs to structure liquids into complex shapes are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation protects a drug from degradation en route to the tumor. 22 Carbosilane dendritic architecture is versatile for designing functional systems for therapy, 46–49 imaging 50 and nanoparticle decoration. 51–53 Furthermore, the chemical structure of carbosilane dendrons containing two orthogonal functionalities favors the synthesis of amphiphilic derivatives self-organizing into micelles 54–56 or dendrimersomes.…”
Section: Discussionmentioning
confidence: 99%
“…Optimized synthesis of dendrons from carefully adjusted elements results in properties that enable the formation of a bilayers, similar to the liposomes, wherein drugs can be loaded. 21 , 22 The present work focus on triazine–carbosilane dendrimersomes of the second (G2) and third (G3) generation. These compounds have a branched hydrophobic part, a triazine cycle (the protonation of which, depending on the pH of the environment, allows the structure of the dendrimersome to loosen or shorten), a piperazine ring (which plays the role of the linker), and the hydrophilic part.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with micelles, inorganic nanoparticles can be immobile preassembled subunits for structuring hierarchical materials. Liu et al prepared gold nanorods coated with hydrophilic molecules along their sides and thiol-terminated polystyrene on their ends through the first-step assembly. , The gold nanorods can then organize themselves into macromolecule-like assemblies in a second-step assembly process by reducing the polystyrene solubility. The principle of step-growth polymerization is valid for the self-assembly of gold nanorods, showing excellent controllability of the nanorod assembly.…”
Section: Introductionmentioning
confidence: 99%